Menjembatani Bahasa dan Budaya: Memanfaatkan 'Manjing Ajur Ajer' Sebagai Alat Pembelajaran Bahasa di Sekolah Menengah Atas Indonesia - Efendi, Agus; Tri Widiatmi; R. Adi Deswijaya; Bambang Ikhwanto (Kawruh: Journal of Language Education, Literature and Local Culture, 2024)
This paper examines the representation of the proverbmanjing ajur ajer as used in a number of articles using the proverbmanjing ajur ajer. The aim is to explore the relevance of the values in the proverbs as a means of achieving educational goals. Using a qualitative approach themanjing ajur ajer proverbs selected from written and oral sources were studied. Although used in different contexts the use of these proverbs can largely be interpreted as character education values in positive attitude and behavior. It is also argued thatmanjing ajur ajer proverbs are represented positively, such representation is seen as a virtue. This research contributes practically to the achievement of students' affective competence.